Pengaruh Sidik Jari (Finger Print) dan Motivasi Kerja terhadap Kedisiplinan Pegawai pada PT Asda Perkebunan Aek Buru Selatan - Sagala, Indriyani Sahfitri; Ulya, Basyarul; Zunaedi, Endy (VISA: Journal of Vision and Ideas, 2025)
This research aims to analyze the influence of the fingerprint attendance system and work motivation on employee discipline at PT ASDA Perkebunan Aek Buru Selatan. This study uses a quantitative approach with multiple linear regression methods. The research sample consisted of 34 employees of PT ASDA Perkebunan Aek Buru Selatan. The results showed that both the fingerprint attendance system and work motivation had a positive and significant influence on employee discipline. Specifically, work motivation was found to have a more dominant influence than the fingerprint attendance system. This research concludes that the use of the fingerprint attendance system and increased work motivation can be effective strategies for improving employee discipline in a plantation environment.